6CN‐driven routing and content delivery scheme for building the smart physical education. Issue 5 (13th September 2020) - Xu, Long; Liu, Wei; Anwlnkom, Tomley; Jinonic, Satamial
Abstract : The development of smart physical education is subject to the large transmission delay from providers to consumers due to the large‐scale and cross‐domain network deployment. In this letter, we propose 6CNRD, a novel system framework based on IPv6 Content Networking (6CN) to facilitate the building of smart physical education. 6CNRD consists of two parts, that is, one is the content request stage based on segment routing, and the other one is the content delivery stage based on identity forwarding. We compare 6CNRD with two cutting‐edge schemes over a constructed physical education topology, and the experimental results show that 6CNRD has lower routing delay and delivery delay. It further indicates that 6CNRD has the wide application value including but not limited to the field of smart physical education. Abstract : The system framework consists two modules, that is, content request based on segment routing and content delivery based on identity forwarding. The first module is responsible for sending requests from consumer to the top provider, and the second module is used for delivering the teaching content to consumer.